Enrolling in Clinical Research While Incarcerated: What Influences Participants' Decisions?. Issue 2 (March 2017) - Christopher, Paul P.; Garcia‐Sampson, Lorena G.; Stein, Michael; Johnson, Jennifer; Rich, Josiah; Lidz, Charles
Abstract: As a 2006 Institute of Medicine report highlights, surprisingly little empirical attention has been paid to how prisoners arrive at decisions to participate in modern research. With our study, we aimed to fill this gap by identifying a more comprehensive range of factors as reported by prisoners themselves during semistructured interviews. Our participants described a diverse range of motives, both favoring and opposing their eventual decision to join. Many are well‐recognized considerations among nonincarcerated clinical research participants, including a desire for various forms of personal benefit, altruism, and concern about study risks and inconveniences. However, a number of influences seem unique to prisoners. Participants did not report that they were not coerced into enrolling, and they have even been under pressure not to enroll. However, many sought to enroll in order to obtain access to better health care, raising a concern about whether they were unfairly exploited.